2020
DOI: 10.11606/s1518-8787.2020054001750
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cryotherapy, cold cone or thermocoagulation compared to LEEP as a therapy for cervical intraepithelial neoplasia: Systematic review

Abstract: OBJECTIVES: To determine the efficacy and safety of the use of cryotherapy, cold knife or thermocoagulation compared to Loop Electrosurgical Excision Procedure (LEEP) for the treatment of cervical intraepithelial neoplasia. METHODS: Systematic review with meta-analysis of randomized controlled trials in women with cervical intraepithelial neoplasia undergoing treatment with cryotherapy, cold knife, or thermo-coagulation compared with LEEP, to estimate its efficacy and safety. The search was conducted on MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…For the treatment of precancerous cervical lesions, both ablative methods (cervical cryotherapy, laser ablation) and LEEP excisional methods, cold cone) can be used effectively. Common complications of these procedures reported in the literature, including minor vaginal bleeding in the first 24 h after surgery which was 5.7% for cold cone, 5.4% for LEEP, 0.4% for cryotherapy; minor vaginal bleeding 24 h after surgery which was 8.3, 8.8, and 23.7% for cold cone, LEEP, and cryotherapy, respectively; cervical stenosis (cold cone 7%, LEEP 6.6%, cryotherapy 0.6%); pain (<30% for cold cone, LEEP, or cryotherapy) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of precancerous cervical lesions, both ablative methods (cervical cryotherapy, laser ablation) and LEEP excisional methods, cold cone) can be used effectively. Common complications of these procedures reported in the literature, including minor vaginal bleeding in the first 24 h after surgery which was 5.7% for cold cone, 5.4% for LEEP, 0.4% for cryotherapy; minor vaginal bleeding 24 h after surgery which was 8.3, 8.8, and 23.7% for cold cone, LEEP, and cryotherapy, respectively; cervical stenosis (cold cone 7%, LEEP 6.6%, cryotherapy 0.6%); pain (<30% for cold cone, LEEP, or cryotherapy) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risks of major bleeding were 0.23% and 0.86%, while the risks of major infections were 0.13% and 0.09%, and the risks of pelvic infectious disease were 0.14% and 0.14%, respectively ( 56 ). Another meta-analysis showed that the reporting rate of residual lesions after LEEP was 11.2%, and that after cold knife conization was 6.1% ( 9 ). We found that the current therapeutic vaccines for precancerous cervical lesions had an average effectiveness of 62.48% for HSIL regression (the highest was 72.32%), and the average level of HPV clearance was 48.59% (the highest was 68.18%).…”
Section: Discussionmentioning
confidence: 99%
“…However, complications such as intraoperative and postoperative bleeding, incision infection, cervical stenosis, endometriosis, and intestinal injury may occur ( 7 ). There are also higher risks of disease recurrence ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently in the screening programmes with Papanicolaou (Pap) smears or with other tests we can detect not only early stage cancer but also the pre-cancerous phases known as Cervical Intraepithelial Neoplasia (CIN) as designated in histological samples, or biopsy or known as Squamous Intraepithelial Lesions (SIL) in cytology by Pap smears, which could be of low grade or high grade [ 4 ]. Treatment of pre-cancerous conditions can be almost 100% successful and surgical or chemo-preventive pharmacotherapy can be used to prevent this disabling and destructive disease [ 1 , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%